Kafa’ah dalam Pernikahan Menurut Ibnu Hazm dan Ibnu Quddamah (Studi Kasus di Kecamatan Medan Belawan) - Alizha, Siti Nur (Lembaga Yasin AlSys, 2023)
The main point of this problem is how Kafa'ah is in marriage according to Ibn Hazm and Ibnu Quddamah (Case Study in Medan Belawan District). Data sources consist of primary data, namely data obtained directly from the object of research, as well as interviews. And also secondary data, namely data taken from the results of literature studies in the form of books, documents, laws and regulations and those related to the discussion under study. Based on the results of this study, it can be concluded that the people in Medan Belawan whom the authors interviewed regarding kafa'ah according to them the main criterion is work (wealth). Of the 3 cases that the authors found, 2 cases stated that work (wealth) was the main criterion, while 1 case stated that the quality of religion was the main criterion. Meanwhile, from the perspective of Ibn Hazm and also Ibn Quddamah, they actually speak kafa'ah in their fiqh books. Ibn Hazm is of the view that kafa'ah is only on religious issues (both are Muslim) and there is no kafa'ah on lineage (heredity), according to him all humans are the same, what is different is only their piety. Whereas in Ibn Qudamah, he in his book mentions 5 things in kafa'ah, namely religion, lineage, independence, skills/work and also spaciousness (wealth). However, according to Ibn Qudamah, the most important thing is religion and lineage. Whereas in the remaining 3, according to Ibn Qudamah it is not the main requirement. Therefore, Ibn Qudamah's opinion is stronger and more comprehensive. Given that this kafa'ah itself can be of important value to a marriage. Between Ibn Hazm and also Ibn Qudamah both are based on the Koran, it's just that Ibn Qudamah is based on Qoul Sohaby and also the Hadiths. And much more is in accordance with the kafa'ah described by Ibn Qudamah in Medan Belawan.